Token forces how tiny troop deployments became ubiquitous in UN peacekeeping - Coleman, Katharina Pichler 1975-; Li, Xiaojun 1981- (Cambridge University Press, 2022)
Token forces - tiny national troop contributions in much larger coalitions - have become ubiquitous in UN peacekeeping. This Element examines how and why this contribution type has become the most common form of participation in UN peace operations despite its limited relevance for missions' operational success. It conceptualizes token forces as a path-dependent unintended consequence of the norm of multilateralism in international uses of military force. The norm extends states' participation options by giving coalition builders an incentive to accept token forces; UN-specific types of token forces emerged as states learned about this option and secretariat officials adapted to state demand for it. The Element documents the growing incidence of token forces in UN peacekeeping, identifies the factors disposing states to contribute token forces, and discusses how UN officials channel token participation. The Element contributes to the literatures on UN peacekeeping, military coalitions, and the impacts of norms in international organizations
Title from publisher's bibliographic system (viewed on 24 Nov 2022)
The Significance of Token Forces -- The Ubiquity of Token Forces in UN Peace Operations -- The Diffusion of Token Participation among UN Troop Contributors -- Token Forces from the UN's Perspective
Keywords: United Nations / Peacekeeping forces; Vereinte Nationen -- Peace Keeping Forces; Vereinte Nationen -- Friedensmission; Deployment (Strategy)